The Silent Brand Killer: The Risk Of Brand Dilution On Established Brands - Woker, Samantha (The IIE, 2017)
This dissertation discusses the issue of how a strong brand, which has been established over an extended period of time, involving extensive resources, can be destroyed or diminished due to the actions of competitors; particularly when making use of the strong brand in order to promote their own brand. This may, in the beginning, appear to be a form of flattery but, over time, it can lead to the death of the brand. This phenomenon is known as brand dilution. Through conducting secondary research in the form of desktop research as well as utilising semi-structured, in-depth interviews with brand professionals and legal professionals in the fields of advertising, marketing and branding, this study aimed to determine the value of a strong brand, a comprehensive understanding of the concept of brand dilution, how a brand can become diluted through the actions of competitors, and, finally, the steps that a brand can take in order to avoid becoming diluted. Brand dilution occurs frequently within the marketplace. However, it remains an unfamiliar term. The current marketplace is saturated with choice. Due to the change in the role that competitors play in our modern marketplace and the way in which competitors use established brands in order to establish their own brands, the mechanics and methodologies for defining, protecting, and growing a brand have profoundly changed. These changes need to be understood because branding plays a major role in terms of protecting the organisations that it represents as well as the consumers that it targets. This study reviewed the benefits of having a strong brand, which is predominantly differentiation from competitors, immediate recognition and brand loyalty, and the multiple ways in which competitor actions can lead to the dilution of established brands. These ways include: becoming the generic, comparative advertising, imitation, trademark tarnishment, trademark infringement, and passing-off. However, this study also determined steps viii through which brands can protect themselves from brand dilution. The steps are: • Registering the brand’s unique and distinctive trademark, • Avoid using the brand name to identify an offering, • Create a clear and well-defined brand strategy, • Create an employee handbook, • Protect the brand’s online content, • Set up Google Alerts, • Monitor the macro and micro environments, with a particular focus on the activities of competitors, • Utilise intellectual property measures, • Set up a legal division, and • Seek legal advice from lawyers who specializes in trademark law. Through the research process, it was concluded that brand dilution is not a commonly known term within the marketplace, although, it occurs frequently in many different forms. However, if brands develop an understanding of brand dilution, how it occurs through the actions of competitors and follow the steps provided above, brands should be able to protect themselves from the possibility of becoming diluted.
Keywords: Branding; Brand Equity; Brand Dilution; Comparative Advertising; Brand Differentiation